BV prox-regular sweeping process with bounded truncated variation. (2nd August 2020) - Nacry, Florent; Thibault, Lionel
ABSTRACT: This paper is devoted to the existence and uniqueness of solutions for perturbed sweeping process measure differential inclusions in infinite dimensional setting. The possibly unbounded moving set is prox-regular and controlled only through the truncated Hausdorff-Pompeiu distance. The normal cone involved is perturbed by a kind of Carathéodory mapping satisfying a time-dependent hypomonotonicity assumption on bounded sets. Various properties of the solution mapping are also provided.